Cartografias do imaginário: interpretações geográficas da paisagem brasileira em mapas europeus do séc. XVII - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
This work aims to reflect about the ways in which the representation of the brazilian landscape in Renaissance maps was part of the spatial planning project of spacial ordering of colonial Brazil, using as a source four maps produced during the period of Dutch Brazil and published in the Atlas Maior (1665). The maps chosen are Praefectura de Ciriji Vel Seregipe Del Rey Cum Itapuama, Praefecturae Paranambucae Pars Meridionalis, Praefecturae Paranambucae Pars Borealis, Uma Cum Praefecturae De Itâmaracâ; Praefectura De Paraiba Et Rio Grande, published for the first time in 1647. The maps chosen to analysis are made by the cartographer George Marcgraff, contains drawings of the painter Frans Post, and if reunited those maps compose a map Brasilia Qua Part e Paret Belgis. The central concept of the discussion is the landscape, understood in two distinct ways: the landscape as a phenomenon, referring to the lived space and the experience of the subjects involved with the production of the maps, and the landscape as representation, drawn in the maps and engraving, mediated by the abilities, imaginary and intentionalities of these same subjects. Three theoretical chapters are presented, related to the concept of landscape and its interfaces with different approaches, besides the conceptualization around what is understood as map, thinking its role as object and image, representative of relations of power. The final chapter presents founded results. It was noticed that there are three biases by which the landscape is represented in order to corroborate with the space project of Maurício de Nassau. In addition, cartographic representation has an element that allows us to function as an argument about the richness, nature and potential of the landscape of Dutch Brazil, which would configure a discourse of positivity and good management, thus justifying the dutch presence in colonial Brazil. Finally, considerations are made that discuss the role of landscape representation in Renaissance maps in order to provide elements for a specific type of imagery that praises the Nassavian government for the artistic and cultural perspective, as well as to feed ideas on the good management of Count Nassau which have remained in the popular imagination for centuries.
Keywords: Cartografia histórica; Brasil holandês; Atlas maior; Historical cartography; Dutch Brazil; Atlas maior; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA